Salinity tolerance of the mud clam, Anodontia edentula (Linne, 1758). - Dignadice, Michelle Iwag
The salinity tolerance range of the mud clam, Anodontia edentula, was investigated in the laboratory. The bivalves were exposed to salinities of 10, 20, 25, 35, 40 and 45 ppt for two weeks. They were maintained at ambient temperature and aeration was provided. Salinity, temperature, pH and dissolved oxygen were checked. Mortality and activities of the mud clams exposed to different salinities were monitored everyday. It was observed that all clams survived at 25 and 35 ppt continued their normal activity. Mean percentages survival were 93.33 and 83.33 at salinities of 20 and 40 ppt, respectively, and slight to medium activities were observed at these concentrations. Mud clams exposed to 45 ppt had only 43.33 survival and slight activity was observed until the end of the experimental period. Mortality was greatest at 10 ppt in which the mean percentage survival was only 23.33 whereas less than 25 of the total number of individuals were moving and feeding during the experiment. These results indicate that A. edentula can tolerate salinities ranging from 20 to 40 ppt and it can acclimate faster at 25 and 35 ppt.